EFEKTIVITAS BIMBINGAN BELAJAR DALAM BIMBINGAN DAN KONSELING DI MADRASAH - Mustikawan, Alfin (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
This research study was aimed at revealing the effectiveness of the learning guidance services in the guidance and counseling program, particularly: the application, the effectiveness and (4) the problem arising and its causes. This research was a case study. The data were collected through observations, interviews, documentation, and questionnaire. The data were analyzed using the interactive model and the quantitative descriptive technique. The research findings showed that: (1) the application is effective. As many as 78.78% respondents said that the work of guiding teachers was effective and 68.99% respondents said that subject matter teachers were involved in guiding processes. (2) The results of learning guidance services given academic and nonacademic advantages. As many as 71.52% respondents said that learning guidance services also academic advantages. As many as 86.08% respondents said that learning guidance services also gave non-academic advantages. (3) The problems faced by counselors in applying learning guidance services include the limited time for them to give advice in the classroom and the lack of counselors. These problems are caused by too many class hours for religion lessons and there is no rule for counselors to get into the classrooms. Â